Oesophageal carcinoma demonstrated by whole-body nuclear magnetic resonance imaging. Issue 6263 (14th February 1981) - Smith, F W; Hutchison, J M; Mallard, J R; Johnson, G; Redpath, T W; Selbie, R D; Reid, A; Smith, C C
Abstract : The quality of the images produced by nuclear magnetic resonance (NMR) imaging has steadily improved over the past five years. Images of the head, thorax, and abdomen have clearly shown the normal anatomy. A clinical trial of NMR imaging has therefore been started in Aberdeen to assess its diagnostic accuracy and compare it with conventional radiography and other imaging technique. The first patient examined by whole-body NMR imaging had carcinoma of the oesophagus diagnosed on barium meal examination. A technetium-99m-sulphur colloid liver scan also showed hepatic metastases. NMR imaging showed a large tumour in the lower third of the oesophagus, and areas of increased proton spin-lattice relaxation time (T1) on a section through the liver corresponded with the metastases shown on the radionuclide scan. Increased areas of T1 were present in some vertebrae, and a technetium-99m bone scan confirmed the presence of bone metastases. The NMR images in this patient compared well with the images from other techniques. The continuing clinical trial may show that NMR is an accurate diagnostic aid which will complement existing techniques for diagnosing intrathoracic and intra-abdominal conditions.